Comorbidity and long-term outcome in patients with congenital heart block and their siblings exposed to Ro/SSA autoantibodies in utero. Issue 5 (26th February 2019) - Mofors, Johannes; Eliasson, Håkan; Ambrosi, Aurelie; Salomonsson, Stina; Skog, Amanda; Fored, Michael; Ekbom, Anders; Bergman, Gunnar; Sonesson, Sven-Erik; Wahren-Herlenius, Marie
Abstract : Objective: Congenital heart block (CHB) may develop in fetuses of Ro/SSA autoantibody-positive women. Given the rarity of CHB, information on comorbidity and complications later in life is difficult to systematically collect for large groups of patients. We therefore used nation-wide healthcare registers to investigate comorbidity and outcomes in patients with CHB and their siblings. Methods: Data from patients with CHB (n= 119) and their siblings (n= 128), all born to anti-Ro/SSA-positive mothers, and from matched healthy controls (n= 1, 190) and their siblings (n= 1, 071), were retrieved from the Swedish National Patient Register. Analyses were performed by Cox proportional hazard modelling. Results: Individuals with CHB had a significantly increased risk of cardiovascular comorbidity, with cardiomyopathy and/or heart failure observed in 20 (16.8%) patients versus 3 (0.3%) controls, yielding a HR of 70.0 (95% CI 20.8 to 235.4), and with a HR for cerebral infarction of 39.9 (95% CI 4.5 to 357.3). Patients with CHB also had a higher risk of infections. Pacemaker treatment was associated with a decreased risk of cerebral infarction but increased risks of cardiomyopathy/heart failure and infection. The risk of systemic connective tissue disorder was also increased in patients with CHB (HR 11.8, 95% CI 4.0 to 11.8), and both patients with CHB and their siblings had an increased risk to develop any of 15 common autoimmune conditions (HR 5.7, 95% CI 2.83 to 11.69 and 3.6, 95% CI 1.7 to 8.0, respectively). Conclusions: The data indicate an increased risk of several cardiovascular, infectious and autoimmune diseases in patients with CHB, with the latter risk shared by their siblings.